2012
DOI: 10.1113/jphysiol.2011.224931
|View full text |Cite
|
Sign up to set email alerts
|

The upright posture improves plantar stepping and alters responses to serotonergic drugs in spinal rats

Abstract: Key points• Locomotor training of rats held in an upright posture has been used recently to restore locomotion after spinal cord injury. Our results show that the upright posture alone improves locomotor recovery in spinal rats.• This improvement is reversed by the removal of cutaneous afferent feedback from the paw, showing that sensory feedback from the foot facilitates the spinal central pattern generator (CPG) for locomotion.• 5-HT 2 and 5-HT 1A/7 agonists improve locomotion in the horizontal posture but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 48 publications
4
89
0
Order By: Relevance
“…We exploited this concept to design an electrochemical neuroprosthesis (3) and training procedures (4,5) that restored full weight-bearing locomotion in rats with a complete spinal cord injury (SCI). Sławińska et al, as well as many others (6,7), reported comparable observations in mice (8), rats (9), and cats (10) over the past three decades.…”
supporting
confidence: 55%
“…We exploited this concept to design an electrochemical neuroprosthesis (3) and training procedures (4,5) that restored full weight-bearing locomotion in rats with a complete spinal cord injury (SCI). Sławińska et al, as well as many others (6,7), reported comparable observations in mice (8), rats (9), and cats (10) over the past three decades.…”
supporting
confidence: 55%
“…It is well established that the basic pattern of locomotion is produced by a specialized network within the spinal cord, the so-called locomotor central pattern generator (CPG) (reviewed in Frigon 2012;Kiehn 2011;McCrea and Rybak 2008). The presence of a spinal locomotor CPG working in concert with sensory feedback from the periphery allows recovery of hindlimb locomotion following complete spinal transection either spontaneously or with training in many mammalian species, such as mice (Leblond et al 2003), rats (Slawinska et al 2012), cats (Barbeau and Rossignol 1987;Lovely et al 1986), and dogs (Naito et al 1990). Spinal cord-transected (spinalized) animal models are powerful tools to assess spinal mechanisms of locomotor control and examine how sensory feedback interacts with spinal circuits during real stepping movements.…”
mentioning
confidence: 98%
“…The upright position itself can improve stepping. 29 Training was also accomplished with manual assistance, which may differ from robotic assist strategies and is discussed elsewhere. [30][31][32][33] Lastly, more repetition and practice facilitates training efficacy 34 ; thus, we opted for hour-long sessions.…”
mentioning
confidence: 99%